EVOLUTION OF THE DEVELOPMENT OF CONCEPTS OF THE CORPORATE SOCIAL RESPONSIBILITY - Erniyazova A.A.,; Taspenova G.A., (Academic Journal of Physical and Chemical Sciences, 2020)
The significance and priority of corporate social responsibility problems are due to, firstly, the high degree of economic development of the leading countries of the world, creating material opportunities to maintain modern standards of living standards of the population; secondly, by strengthening the role of intangible factors of economic growth associated with the need for investment in human capital as a key condition for innovative economic growth based on the potential of intelligence, education and creativity of workers. An important reason for increasing attention to the development of the social functions of the entrepreneurial community in Kazakhstan was the revision of traditional views on the concept of social policy in the direction of expanding the circle of its subjects and significantly reducing government intervention in solving many socio-economic problems. The growing interest in the problem of corporate social responsibility (CSR) requires a deep understanding of this concept to develop measures for the practical implementation of socially responsible behavior of business structures. An analysis of the genesis and content of the basic concepts of CSR allows us to identify “nuclear” and alternative theories that make it possible to identify various aspects of CSR. The article analyzes the main approaches that have emerged in the work of Western CSR researchers, an attempt is made to systematize these approaches based on the ratio of their essence and theoretical content. The article discusses various interpretations of the term "corporate social responsibility", explores its specificity. The principles and levels of business social responsibility are set out in detail. Particularly emphasized is the role of corporate social reporting as an effective tool for dialogue between business with society and the state.